2006
DOI: 10.1074/jbc.m513629200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of FOXC1 Stability and Transcriptional Activity by an Epidermal Growth Factor-activated Mitogen-activated Protein Kinase Signaling Cascade

Abstract: Mutations in the FOXC1 transcription factor gene result in Axenfeld Rieger malformations, a disorder that affects the anterior segment of the eye, the teeth, and craniofacial structures. Individuals with this disorder possess an elevated risk for developing glaucoma. Previous work in our laboratory has indicated that FOXC1 transcriptional activity may be regulated by phosphorylation. We report here that FOXC1 is a short-lived protein (t1 ⁄ 2 <30 min), and serine 272 is a critical residue in maintaining proper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 28 publications
2
45
0
Order By: Relevance
“…Furthermore, these residues are also conserved in the related transcription factor FOXC1, suggesting that both TFs may be similarly regulated by phosphorylation. In accordance with this possibility, half (4 of 8) of the conserved phosphorylation sites have already been experimentally confirmed in FOXC1 (29,31,32). These findings once again underscore the importance of phosphorylation in the regulation of FOXC2-and FOXC1-mediated transcription and further imply that the regulation involves complex molecular interactions, rather than simple addition of cGOF , and FOXC2 ecGOF embryos.…”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, these residues are also conserved in the related transcription factor FOXC1, suggesting that both TFs may be similarly regulated by phosphorylation. In accordance with this possibility, half (4 of 8) of the conserved phosphorylation sites have already been experimentally confirmed in FOXC1 (29,31,32). These findings once again underscore the importance of phosphorylation in the regulation of FOXC2-and FOXC1-mediated transcription and further imply that the regulation involves complex molecular interactions, rather than simple addition of cGOF , and FOXC2 ecGOF embryos.…”
Section: Discussionsupporting
confidence: 65%
“…FoxC1 expression is undetectable in adult tissues, but FoxC1 expression is activated by Wnt and EGF/ERK signaling pathway during embryogenesis 10,11 . Recent studies reported that FoxC1 is a master regulator of cancer invasion and metastasis.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…It is likely that the dramatic overexpression of Foxc1 in our transfection assays is the reason for the apparently normal transactivation by mutant protein in our transcriptional assays. Stability of Foxc1 has been linked to the C-terminal phosphorylation of the protein (27), and evaluation of the phosphorylation state of F107L-Foxc1 protein revealed reduced phosphorylation compared with wildtype controls (Fig. 3e).…”
Section: Resultsmentioning
confidence: 99%